Efecto del anillado y aplicación de fitohormonas en la floración, cuajado y crecimiento de frutos en plantas de naranja en el Centro Binacional Zapotepamba de la provincia de Loja. - Córdova Vivanco, Gustavo Israel (2019)
The present study was carried out at Zapotepamba Experimental Station of the Universidad Nacional de Loja. Its purpose was to evaluate the effect of ring bound as well as the application of phytohormones in the blooming, and fruits setting and growing of orange plants. A completely random experimental sampling design was established on twelve-year-old adult orange trees (Citrus sinensis L.) at the same phenologic period, planted at a linear distance of 4 m. The experimental unit had one tree and each treatment had four repetitions. In every orange tree, four experimental branches were chosen, distributed according to the four cardinal points. Each one was labeled and codified. The variables to be measured were: number of days at the beginning of the blooming, number of flowers, number of fruits setting, fruit size, and abscission. The results showed that the ring bound had an effect in the acceleration of the floral differentiation 35 days after the treatment (DAT), with a measure of 8.81 flowers buds/branch, in relation with the other treatments that were 49 days after the treatment. The ring bound favored the flower inducement 70 DAT with more flowers, reaching a median of 30.39 flowers/branch. The application of phytohormones (Maxi-Grow) did not present a major effect in relation with the rest of the treatments, as well as the combination of ring bound and phytohormones. The ring bound produced more fruits held 98 DAT, with a median of 59.31 fruits/branch, compared with the combination of ring bound and Phytohormones (A. Giberélico and Maxi Grow) and the use of Phytohormones only. The combination of ring bound and Phytohormones (Ring bound plus Maxi-Grow) was found to have a meaningful effect by favoring a fruit/branch big size and weight 124 DAT. Either the ring bound or the Phytohormones alone did not present a major effect. Finally, the combination of ring bound and phytohormones presented more number of fruits held, in comparison with either the ring bound or the phytohormones alone. Key words: ring bound, phenologic stage, phytohormones, floral differentiation, floral inducement.